Prevalence and associated factors of caregiving burden among caregivers of individuals with severe mental illness: A hospital based study at St John of God Hospitaller services in Mzuzu, Malawi - Banda, Richard (Department of Psychiatry and Mental Health, 2020)
Background: Severe mental illnesses (SMI) cause significant impairment for those living with the illnesses and often rely on caregivers for the ongoing care. Available evidence suggests that individuals responsible for caregiving may get distressed due to the caregiving experience, a phenomenon researchers call caregiver burden. Following the shift to community-centered mental health services, several studies on caregiving burden have been conducted in high income countries (HIC). However, there remains scarcity of data on the subject in SubSaharan Africa including Malawi. Therefore, the present study investigated the prevalence and associated factors of caregiving burden among caregivers of individuals with SMI at St John of God Hospitaller Services (SJOGHS) in Mzuzu-Malawi. Methods: The study adopted a hospital based cross sectional study. Recruitment took place at two outpatient departments of SJOGHS. Informal caregivers who were 18 years and above were asked to participate. The study recruited 139 caregivers and two research assistants approached participants at the waiting area. Caregivers who gave consent were asked questions about their caregiving activities using the Zarit Burden Interview (ZBI) (maximum score, 88). Data analysis was done using frequency distributions and descriptive statistics. The study used non-parametric tests such as a chi-square on all categorical measurements to test associations between variables and parametric tests such as t test on all continuous variables. The unadjusted and adjusted associations between socio-demographic factors and caregiving burden was conducted using logistic regression models. Results: On average, most caregivers experienced mild to moderate caregiving burden on the ZBI score (31.5 ± 16.7). In the adjusted model after controlling for caregivers’ gender, caregivers’ age, level of education, social support, care recipients’ age and care recipients’ gender, only caregivers’ age, social support and care recipients’ age remained significantly associated with caregiving burden. Older caregivers were more likely to experience caregiving burden than younger caregivers (OR=1.03, 95% CI 1.00-1.06), caregivers with social support were 71 % less likely to develop caregiving burden than those without social support (OR=0.29, 95% CI 0.14-0.62) and caregivers of older care recipients were less likely to experience caregiving burden than those of younger care recipients (OR=0.26, 95% CI 0.11-0.64). v Conclusion: Even though the caregiving burden found in this study was low compared to other previous studies in some arguably developed countries such as Iran and Turkey, it remains high in other developing countries such as Ghana and Nigeria. The low burden in this study, could be attributed to several factors and context in which the study was conducted. One such factor is the routine psychoeducation that the hospital often conducts for caregivers during the subsequent monthly reviews of their care recipients. An important follow up would be to investigate caregiving burden among caregivers who are unable to access the services at SJOGHS. The results of this study are important to guide policy in the formation of effective community programs that may assist mitigate the burden of informal caregivers. Finally, to understand the importance and implications of informal caregiving, further studies are needed in Malawi.